2018
DOI: 10.1016/j.jweia.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

CFD investigation on wheel rotation modelling

Abstract: Moving Reference Frame -grooves (MRFg) approach for modelling tyre rotation is presented.• It is validated on a freely rotating isolated wheel against the sliding mesh approach.• The prediction of tyre pattern modifications using MRFg shows good agreement with experimental measurements on a full scale vehicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…The results are based on a simulation performed by Hobeika et. al [26], simulating a driving condition of 100 km/h with zero yaw, using a hybrid RANS-LES turbulence modelling approach and with an Improved Delayed Detached Eddy Simulation (IDDES) formulation. Three seconds of physical time were computed, before the time averaged results over two seconds were calculated.…”
Section: Completion Of the Flow Field Picture With Cfdmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are based on a simulation performed by Hobeika et. al [26], simulating a driving condition of 100 km/h with zero yaw, using a hybrid RANS-LES turbulence modelling approach and with an Improved Delayed Detached Eddy Simulation (IDDES) formulation. Three seconds of physical time were computed, before the time averaged results over two seconds were calculated.…”
Section: Completion Of the Flow Field Picture With Cfdmentioning
confidence: 99%
“…The total mesh size was approximately 120 million cells. The detailed setup, as well as the results of a mesh and time step study can be found in Hobeika et al [26]. gives also the information about the sense of rotation.…”
Section: Completion Of the Flow Field Picture With Cfdmentioning
confidence: 99%
“…This approach is often used in industrial applications, such as cooling of electrical components [1,2], ventilation [3,4], tidal current turbines [5,6] and automotive applications. In the automotive industry, areas of application are, e.g., the rotation of wheels [7] and of the fan for the cooling system. However, there are limitations to this model.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the complex structures in the wheel wake and their interaction with the vehicle body, many research groups focused their research on wheels and their impact on vehicle aerodynamics. (Wickern et al [1] , Landström et al [2] Wittmeier [3] , Schnepf [4] , Haag [5] , Lew et al, [6] Hobeika [7] and many others. )…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focused on different simulation methods for the rim like Haag et al [5] , Lew et al [6] , Altmann et al [8] Hobeika and Sebben [7] . Comparing the RWBC to Multiple/Moving Reference Frame (MRF) and Sliding Mesh (SM) methods showed, that the SM method gives the best results for simulating the rim.…”
Section: Introductionmentioning
confidence: 99%